PELAKSANAAN FUNGSI KOMITE SEKOLAH PADA SEKOLAH MENENGAH PERTAMA NEGERI SE-KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Ramadhan (Jurnal Bahana Manajemen Pendidikan, 2014)
The goal of this research are to see information about the showed that the performance of the functions of the School Committee. The population is 37 people from School Committee and the sample is 37 people that taken by research population. The instrument of this research is question with Likert Scale Models that had tested for validity and reliability. Data analyzed using mean score and performance level. The result of this research are the showed that the performance of the functions of the School Committee in SMP Negeri Se- Kecamatan Bayang Kabupaten Pesisir Selatan stay in good enough category. Keyword : School Committee